Antibiotic resistance profile and RAPD analysis of Campylobacter jejuni isolated from vegetables farms and retail markets - Huat, J.T.Y.; Che Abdullah, Abu Bakar; Mohd Ikhsan, Khalid; Syazana Aimi, .; Son, Radu (2015)
Objective: To investigate antibiotic resistance profile and characterize Campylobacter jejuni (C. jejuni) isolates using random amplified polymorphic DNA (RAPD) analysis. Methods: Ninety eight C. jejuni isolates from farms and retail outlets were screened against 10 antibiotics commonly used clinically and agriculturally by using disk diffusion method. RAPD analysis was done to characterize 98 C. jejuni isolates. Results: Fifty-one percent of the isolates had multiple antibiotic resistance index 0.2 and below. This indicated that the isolates in the vegetables were not from the high risk environment or extensive farming practices. C. jejuni isolates found resistant towards penicillin G (93%), vancomycin (86%), ampicillin (35%), erythromycin (28%), gentamycin (4%), amikacin (3%), enrofloxacin (1%), norfloxacin (1%) and no resistance towards ciprofloxacin. RAPD clustering analysis showed that the contamination of C. jejuni in vegetables was likely due to cross contamination at retail markets. Conclusions: C. jejuni contamination in vegetables at retail markets was due to cross contamination. Current finding proved that C. jejuni in small scale vegetables production was less expose towards antibiotic abuse.